IDENTIFIKASI BAKTERI DAN ANALISIS AKTIVITAS ENZIM PADA ISOLAT PB 16.2 DALAM BIODEGRADASI POLYURETHANE FOAM - PRAMITHA AYU KINANTI (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
The increasing production of polyurethane foam in various industrial sectors has led to the accumulation of waste that is difficult to degrade and has the potential to cause environmental pollution. One environmentally friendly approach that can be used to overcome this problem is biodegradation using microorganism bacteria. This study aims to identify the bacterial isolate PB 16.2 and analyze its enzyme activity in the biodegradation process of polyurethane foam. The study was conducted through a 30-day biodegradation test with sampling every 10 days. The research methods include measuring bacterial growth using OD₆₀₀, analyzing the enzyme activities of laccase, lipase, protease, urease, and esterase, and calculating the percentage of weight loss of polyurethane foam. Changes in substrate characteristics were described using FTIR, XRD, SEM, and DSC. Identification of bacteria was carried out morphologically through Gram staining and molecularly using 16S rRNA gene analysis. The results showed that isolate PB 16.2 was able to grow by utilizing polyurethane foam as a carbon source, which was caused by an increase in the number of bacterial cells, dominant enzyme activity, especially lipase, as well as a decrease in weight and changes in the physical-chemical characteristics of polyurethane foam. Based on these results, the bacterial isolate PB 16.2 has the potential as a biodegradation agent for polyurethane foam.
biodegradasi, identifikasi
Keywords: biodegradation; polyurethane foam; bacterial isolate PB 16.2; enzyme activity; 16S rRNA